“Whomever You Find, Invite”: The Parable of the Great Supper (Q 14:16–21, 23) and the Redaction of Q - Howes, Llewellyn (Neotestamentica, 2015)
In The Formation of Q, Kloppenborg identifies three redactional layers in the Sayings Gospel Q: the “formative stratum” (or Q1), the “main redaction” (or Q2), and the “final recension” (or Q3). He ascribes Q 14:16-24 to the main redaction. As an alternative, this article argues that the passage in question appeared in the formative stratum before it was incorporated into the main redaction.